Parâmetros físicos-hídricos de um latossolo sob diferentes sistemas de manejo e níveis de tráfego - Fontanela, Eracilda (2008)
Soil quality has been widely studied since the soil is recognized as a key resource in agricultural production. Thus, it is necessary to assess a range of indicators of soil quality, in order to monitor parameters that indicate quality or soil degradation in agricultural activities. The objective was to assess indicators of physical and hydrical soil quality, for different soil tillage, management and levels of traffic. The specific objectives were: to determine critical limits of soil density where mechanical penetration resistance and aeration porosity are restrictive to crop growth, using a methodology of the least limiting water range (LLWR); evaluate plant water available in different states of soil compaction with the period in which the soil moisture is below or above the physical conditions considered optimal, determined by the LLWR; evaluate soil compaction through the parameters of soil compressibility; and verify relationships between air permeability, continuity of soil pores and water retention curve. The experiment was established in 2001 in an Oxisol, in the experimental station of Embrapa Trigo in Passo Fundo-RS. The soil management under study were: chisel plowed six months ago, chisel plowed twelve months ago, chisel plowed eighteen months ago, continuous no-tillage for 13 years, and native forest; all with and without traffic. Soil sample were collected with preserved structure in each treatment, in both levels of traffic, in three soil layers (0.00-0.06, 0.10-0.15, and 0.20-0.25m). The soil samples were equilibrated at -0004, - 0006, -0008, -0.01, -0.03, -0.05, -0.07, -0.1, -0.5 and -1.5MPa and then used for determining soil bulk density, resistance to penetration, volumetric moisture, and air conductivity. The soil compression curve was obtained in the tension of 0.03MPa. Increased bulk density caused a reduction in the LLWR associated to the effects of soil resistance to penetration and aeration porosity that, respectively, determined the lower and upper limits of available water. The chisel plow treatment had lower physical restriction based on the resistance to penetration, with a value of critical soil density equal 1.60Mg m-3. The LLWR was more sensitive to changes in soil structure than the available water, reflecting better physical quality of the soil for the growth of crops. Air permeability showed high variability that can be observed by the change in bulk density and by the relationship with the matric potential and pore size distribution. The low values of pore continuity index indicate reduced pore space and low presence of large pores. The preconsolidation stress was not affected by the different soil managements. Susceptibility to soil compaction showed statistical interaction between the soil management and traffic in the two uppermost soil layers (0.00-0.06 and 0.10-0.15m). Therefore, the physical and hydrical indicators were influenced by changes in soil structure. Traffic on chisel plowed soil had greater influence on those indicators.